Money and fiscal policies under floating and/or fixed exchange rate regimes - Jones-Hendrickson, S. B. (Caribbean Centre for Money & Finance [St. Augustine]TT, 2002)
Discusses the approaches of a Floating Exchange Rate or a Fixed Exchange Rate in the context of money and fiscal policies. Concludes that the rates tend to be dependent upon the specific behaviour conditions and historical periodicity.